New species and records of Leptusa Kraatz from the Iberian peninsula (Insecta: Coleoptera: Staphylinidae, Aleocharinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Two species of Leptusa Kraatz are described from northwestern Spain: L. (Pisalia) cavata sp. n. and L. (Gnopheropisalia) cremata sp. n. Their facies and sexual characters are illustrated. New distribution data are presented for 16 species, most of which have not been recorded since their original descriptions, including the first record of L. nigerrima from Portugal.KeywordsColeoptera, Staphylinidae, Aleocharinae, Leptusa, Palaearctic, Europe, Spain, Portugal, taxonomy, new species, new records.Nomenclatural Actscremata Assing, 2003 (Leptusa (Gnopheropisalia)), spec. n.cavata Assing, 2003 (Leptusa (Pisalia)), spec. n.